Achievement Motivation and the Students’ Speaking Performance - Yuni - Astuti (Fakultas Ilmu Budaya, Universitas Brawijaya, 2019)
This study employs a correlational design that is to find out the relationship between achievement motivation and the students’ speaking performance. The aim of this study obtains the level of students’ achievement motivation and their speaking performance. This study also reveals the relationship between the variables. The questionnaire with four Likert-scale was used to measure the students’ level in this study. It was the adaptation of the Contextual Achievement Motivation questionnaire. To measure the students' speaking performance, a teacher-made speaking test was used. The questionnaire and the speaking test were administered to undergraduate second-semester students of the English Department, Faculty of Cultural Studies, Universitas Brawijaya. The result of this study showed that there was a significant average positive correlation between achievement motivation level and the students’ speaking performance level (r = .688, sig. = .00). Regarding the result of the students' learning in the speaking class, teachers are expected to be able to recognize their students’ achievement motivation to support and enhance the students' ability in learning. Teachers are expected to encourage the students to be more open and share their difficulties in learning especially in the speaking class. Thus, by having close communication between teachers and the students, it is expected that the students’ problems during the learning process can be solved. The students’ achievement motivation is expected to be higher and stronger in completing the course with high achievement.